2017
DOI: 10.1167/iovs.17-22522
|View full text |Cite
|
Sign up to set email alerts
|

Association Between Serum Complement C3 Levels and Age-Related Cataract

Abstract: ARC patients have lower serum C3 levels, which were further demonstrated to be correlated with the onset/development of ARC. These findings suggest the involvement of C3 in the pathomechanisms of ARC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 29 publications
(33 reference statements)
0
3
0
Order By: Relevance
“…As the promoter of the classical complement cascade, C1q is the key modulation node of this pathway. Some studies have shown that the amount of complement C3 in the peripheral blood of sick patients with congenital cataracts is dramatically decreased, and the reduction of complement C3 is a risk factor for congenital cataracts (Shi et al 2003 ; Ge et al 2014 ; Shao et al 2017 ; Li et al 2017 ). In addition, complement deposition was also observed in the lens of mice with inflammatory damage (Montalvo et al 2007 ).…”
Section: Discussionmentioning
confidence: 99%
“…As the promoter of the classical complement cascade, C1q is the key modulation node of this pathway. Some studies have shown that the amount of complement C3 in the peripheral blood of sick patients with congenital cataracts is dramatically decreased, and the reduction of complement C3 is a risk factor for congenital cataracts (Shi et al 2003 ; Ge et al 2014 ; Shao et al 2017 ; Li et al 2017 ). In addition, complement deposition was also observed in the lens of mice with inflammatory damage (Montalvo et al 2007 ).…”
Section: Discussionmentioning
confidence: 99%
“…If both eyes suffered from ARC, only one eye was randomly selected for the study. The final sample consisted of 219 ARC patients who met the following inclusion criteria as described previously 13 : age ≥45 years; ARC recorded using the Lens Opacities Classification System III; ARC defined as the presence of any type of ARC (cortical, nuclear or PSC) or a history of cataract surgery (pseudophakic or aphakic eyes) in either eye; no history of secondary cataracts, congenital cataracts or any other eye diseases and no history of systemic diseases such as acute infectious diseases, kidney disease, autoimmune disease and cancer.…”
Section: Methodsmentioning
confidence: 99%
“…Of these, 32 normal subjects (cataract=5, cancer=2, renal disease=6, liver disease=4, autoimmune disease=2, macular degeneration=3, cardiovascular disease=4, other diseases=6) were later excluded from the study based on the inclusion criteria. The final sample consisted of 218 control subjects who met the following previously described criteria 13 : age ≥45 years; no history of any types of cataracts, secondary cataracts, congenital cataracts and any other eye diseases and no history of systemic diseases such as acute infectious diseases, kidney disease, autoimmune disease and cancer.…”
Section: Methodsmentioning
confidence: 99%